RESPONSES OF SOME NEW ROMANIAN POTATO VARIETIES TO THE IN VITRO HIDRIC STRESS - Manuela Hermeziu; Andreea Tican; Maria Iamandei (Agricultura, 2021)
Plant performance and crop yield are negatively affected by drought and heat in the context of the global climate changes.